2015
DOI: 10.1155/2016/1792573
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Self‐Renewal and Pluripotency in J1 Mouse Embryonic Stem Cells through Regulating Transcription Factor and MicroRNA Expression Induced by PD0325901

Abstract: Embryonic stem cells (ESCs) have the ability to grow indefinitely and retain their pluripotency in culture, and this self-renewal capacity is governed by several crucial molecular pathways controlled by specific regulatory genes and epigenetic modifications. It is reported that multiple epigenetic regulators, such as miRNA and pluripotency factors, can be tightly integrated into molecular pathways and cooperate to maintain self-renewal of ESCs. However, mouse ESCs in serum-containing medium seem to be heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The expression of miR296-3p was decreased in SC1-treated mouse ES cells, and was increased during ES cell differentiation [59]. Previous experiments also confirmed that transfection of miR-296 mimics suppressed Nanog levels in J1 mouse ES cells [37]. …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The expression of miR296-3p was decreased in SC1-treated mouse ES cells, and was increased during ES cell differentiation [59]. Previous experiments also confirmed that transfection of miR-296 mimics suppressed Nanog levels in J1 mouse ES cells [37]. …”
Section: Discussionmentioning
confidence: 90%
“…PD0325901(PD) is an inhibitor of the MEK/ERK pathway. Our previous study reported small RNA deep-sequencing results from PD-treated mouse ES cells [37]. Therefore, the general differences in differentially expressed microRNAs in SC1- and PD-treated mouse ES cells were analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It turns out that these two inhibitors, in general, even regulate the miR processing significantly by influencing the two important miR processors DGCR8 and Drosha, respectively. Recent reports suggest that MEK/ERK can phosphorylate DGCR8, which increases its intracellular stability and hence induces a pro-growth miR profile [52,53]. On the other hand, GSK3 phosphorylates the Drosha and increases its nuclear localization [54][55][56].…”
mentioning
confidence: 99%